Efficiency enhancement by mixed cation effect in dye-sensitized solar cells with a PVdF based gel polymer electrolyte - Mohd Arof, Abdul Kariem; Aziz, M. F.; Mohd Noor, Mazni; Careem, M. A.; Bandara, L. R A K; Thotawatthage, C. A.; Rupasinghe, W. N S; Dissanayake, M. A.K.Lakshman (Elsevier Limited, 2014)
This paper reports the effect of using a mixed iodide salt system with two dissimilar cations to enhance the efficiency of dye-sensitized solar cells made with polyvinylidenefluoride (PVdF) based gel electrolyte. Instead of a single iodide salt, a mixture of potassium iodide (KI) with a small K+ cation and tetrapropylammonium iodide (Pr4NI) with a bulky Pr 4N+ cation were used to provide the required iodide ion conductivity. Solar cells of configuration FTO/TiO2/Dye/electrolyte/ Pt/FTO were fabricated using a mesoporous TiO2 electrode sensitized with a Ruthenium dye (N719). With identical electrolyte compositions, the cells with KI and Pr4NI alone gave efficiencies of 2.37% and 2.90% respectively. The cell with the mixed iodide system, KI:Pr4NI = 16.6:83.4 (% weight ratio), however, showed an enhanced efficiency of 3.92% with a short circuit current density of 9.16 mA cm-2, open circuit voltage of 674.4 mV and a fill factor of 63.4%.